2013
DOI: 10.1007/s12275-013-3344-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface expression of Aspergillus saitoi-derived functional α-1,2-mannosidase on Yarrowia lipolytica for glycan remodeling

Abstract: Expression of proteins on the surface of yeast has a wide range of applications, such as development of live vaccines, screening of antibody libraries, and use as whole-cell biocatalysts. The hemiascomycetes yeast Yarrowia lipolytica has been raised as a potential host for heterologous expression of recombinant proteins. In this study, we report the expression of Aspergillus saitoi α-1,2-mannosidase, encoded by the msdS gene, on the cell surface of Y. lipolytica. As the first step to achieve the secretory expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…All of these tools have been successfully used in Y. lipolytica to produce such proteins as xylanase, lipase, leucine aminopeptidase II, human interferon, α2b endoglucanase II, and cellobiohydrolase II [ 6 , 9 , 14 , 19 , 20 ]. Past studies have also identified at least three sequences that can be used to optimize protein secretion in Y. lipolytica : preLip2, preXpr2, and preSuc2 [ 6 , 14 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these tools have been successfully used in Y. lipolytica to produce such proteins as xylanase, lipase, leucine aminopeptidase II, human interferon, α2b endoglucanase II, and cellobiohydrolase II [ 6 , 9 , 14 , 19 , 20 ]. Past studies have also identified at least three sequences that can be used to optimize protein secretion in Y. lipolytica : preLip2, preXpr2, and preSuc2 [ 6 , 14 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discussed above studies aimed at expanding native substrate range of the species to highly abundant polysaccharides, i.e., starch, cellulose, xylan, and inulin. Due to the review capacity, at least several highly promising issues had to be neglected, like acquired capacity to decompose pectins by overexpression of polygalacturonase (Muller et al 1998), or glucomannan, through surface display of mannosidase (Moon et al 2013). Based on conducted literature search and own experience, the key challenge in developing Y. lipolytica-based consolidated biocatalysts is balancing optimal conditions for the host growth and the enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…This C-terminal part of CWP1 gene corresponds to a GPI anchor domain, namely a signal for the posttranslational addition of a GPI (glycosylphosphatidylinositol) structure to the secreted protein and for its covalent linking to β-1,6 glucans from the yeast cell wall (surface display). As reviewed previously [ 20 ], a few other GPI anchoring signals from Y. lipolytica cell wall proteins have also been applied to surface display in this yeast [ 250 , 251 , 252 ], but the OUC/INRA zeta-based auto-cloning pINA1317-CWP110 surface display expression vector [ 221 ] remains up to now the more widely used tool for constructing arming Y. lipolytica cells.…”
Section: A Brave New World Of Engineered Strains: Tools and Strategies For Building Y Lipolytica Cell Factoriesmentioning
confidence: 99%